ANALISIS REKLAMASI VENUE DAYUNG DI TELUK YOUTEFA KOTA JAYAPURA - Fred Andris Waroy; Johni J Numberi; Janviter Manalu (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2021)
The coastal area is one of the potential resources. The coastal area has the meaning of a transitional area between land and sea. According to Law No. 27 of 2007 Article 34 concerning the management of coastal areas and small islands, reclamation of coastal areas and small islands is carried out in order to increase the benefits and / or added value of coastal areas and small islands in terms of technical, environmental and socio-economic aspects. a research method consists of procedures and techniques that need to be carried out in a study. In connection with the coastal reclamation carried out in Youtefa Bay, Jayapura City, which is in the context of completing the 2021 PON in Papua Province. Jayapura City is the capital city of Papua Province which will be used as one of the places for the implementation of PON 2021 in Papua Province, so that several sports suggestions have been built in the city of Jayapura, one of which is the Rowing Venue facility built in Youtefa Bay, Jayapura City, this arena sports branch This research was conducted in Youtefa Bay (Holtekamp), administratively in the area of Jayapura City, Entrop Village, South Jayapura District. This infrastructure development is considered very important for the community because it can indirectly increase the living capital of those who live around the area. There needs to be extensive reforestation of mangrove forests that have been logged.